The Effect of Auditor Switching and Financial Distress on Audit Report Lag in Non-Primary Consumer Goods Companies Listed on the Sharia Securities List (DES) in 2021-2024 - Amalia Marliani; Dudang Gojali; Gina Sakinah (Journal of Applied Accounting, 2026)
This research is motivated by the persistence of companies that submit audited financial reports late despite being regulated by the Financial Services Authority Regulation No. 14/POJK.04/2022 concerning the deadline for submitting financial reports. Companies in the Non-Primary Consumer Goods sector listed on the Sharia Securities List are among the sectors with the highest audit report lag rates in the 2021–2024 period. This study aims to analyze the effect of auditor switching on audit report lag, the effect of financial distress on audit report lag, and the simultaneous effect of auditor switching and financial distress on audit report lag. The research method used is quantitative with secondary data in the form of annual financial reports of companies in the Non-Primary Consumer Goods sector listed on the Sharia Securities List (DES) for the 2021–2024 period. The research sample consisted of 19 companies selected using a purposive sampling technique. The results show that (1) auditor switching has a significant positive effect on audit report lag, (2) financial distress does not have a partial significant effect on audit report lag, and (2) auditor switching and financial distress have a simultaneous significant effect on audit report lag. Keywords : auditor switching, financial distress, audit report lag